Improving Student Learning Outcomes with Project Based Learning Chemical Elements - Rafini Rafini; Sugiharti Sugiharti; Tri Rahayu (FITK UIN Walisongo Semarang, 2023)
Classroom action research using a project based learning model with a power point media creation project on chemical elements aims to improve student learning outcomes. Using the project based learning model can actively involve students in the learning process. Assessment can also be carried out comprehensively, starting from cognitive assessment through pretest and posttest. Assessment of attitudes and skills during student presentations and reflections using appropriate research instruments. The results of this classroom action research gave positive results, seen from the increase in students' pretest and posttest scores. The average pretest score is 23.8% and the average posttest score is 67.7%. For the results of the assessment of student presentations which measured attitudes and skills, the data obtained were material readiness reached 94%, attitude during the presentation reached 91% and questions and answers reached 91%. Student reflection on the learning model provides the following data, students like the project based learning learning model with a percentage of 93%, helps solve questions as much as 57%, more actively explores the material during learning as much as 79%, learning is more effective as much as 57% and increases motivation student learning as much as 86%. Learning outcomes increased significantly for cognitive assessment, attitude assessment and skills assessment, which was very good as well as good reflection from students. From the results of this classroom action research, the project based learning method can be an effective method that can be used in learning that produces a product from students' creative work